2017
DOI: 10.1002/jcp.25590
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin‐1 Regulates Adipokine Production in 3T3‐L1 Adipocytes and Adipose Tissue From Obese Mice

Abstract: Cardiotrophin-1 (CT-1) belongs to the IL-6 family of cytokines. Previous studies of our group revealed that CT-1 is a key regulator of glucose and lipid metabolism. The aim of the present study was to analyze the in vitro and in vivo effects of CT-1 on the production of several adipokines involved in body weight regulation, nutrient metabolism, and inflammation. For this purpose, 3T3-L1 adipocytes were incubated with recombinant protein CT-1 (rCT-1) (1-40 ng/ml) for 1 and 18 h. Moreover, the acute effects of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…Lower levels of CT-1 expression are also seen in testis and brain [ 75 ]. Interestingly, adipose tissue has been also identified as a source of CT-1, acting as an adipokine [ 80 , 81 ]. Therefore, CT-1 could act not only in a paracrinic manner, but also as an endocrine factor involved in the regulation of several physiological/pathophysiological functions [ 82 ].…”
Section: Cardiotrophin-1mentioning
confidence: 99%
See 4 more Smart Citations
“…Lower levels of CT-1 expression are also seen in testis and brain [ 75 ]. Interestingly, adipose tissue has been also identified as a source of CT-1, acting as an adipokine [ 80 , 81 ]. Therefore, CT-1 could act not only in a paracrinic manner, but also as an endocrine factor involved in the regulation of several physiological/pathophysiological functions [ 82 ].…”
Section: Cardiotrophin-1mentioning
confidence: 99%
“…Indeed, studies performed in mice have shown that gene expression levels of CT-1 were down-regulated in white adipose tissue from diet-induced obese mice [ 88 , 89 ]. Moreover, plasma levels of this cytokine are elevated in patients with obesity and metabolic syndrome, suggesting that CT-1 could be considered as a marker and a link between adipose tissue, insulin resistance and cardiovascular diseases [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Contrariwise, another study stated that overweight and obese subjects had significantly lower CT-1 levels than those with normal weight [ 92 ].…”
Section: Cardiotrophin-1mentioning
confidence: 99%
See 3 more Smart Citations